Penerapan Weigted product (WP) dalam sistem pendukung keputusan pemetaan pemilihan rumah baru - Putri Pratiwi, Mariska; Fauzi, Rahmat; Hutabri, Elbert; Muharmi, Yulya (Jurnal Nasional Ilmu Komputer, 2025)
The process of selecting a new house is a complex decision that involves careful consideration of multiple interacting criteria, including price, location, building size, facilities, and surrounding environment. In today's competitive real estate market, potential buyers often struggle to make optimal choices due to the overwhelming number of options and factors to consider. An effective decision support system (DSS) is essential to address this challenge. This research implements the Weighted Product (WP) method to systematically map and evaluate alternative choices of new houses based on predetermined criteria. The WP method was specifically chosen for its robust capability in handling multi-criteria decision-making processes where various factors interact and influence each other. The study analyzed data from 50 housing properties across different locations, considering eight key criteria weighted according to buyer preferences. The research methodology included data collection, criteria weighting, WP calculations, and result validation. The findings demonstrate that the WP method successfully provides accurate and reliable results, enabling potential buyers to make well-informed decisions aligned with their preferences. The implemented system showed an 85% satisfaction rate among test users, confirming its effectiveness in simplifying the complex house selection process by systematically evaluating available options.